Political Rivalry in the Light of Leigh van Halen’s Red Queen Hypothesis - Jarosław Nocoń (Politeja)
The Red Queen hypothesis is a popular model for analysing the phenomenon of competition in nature. It establishes mutual dependencies between competing species that stimulate their changes and adaptation processes to new conditions. The result of such competition is a self-propelling race, which allows for the evaluation of its effects, including the benefits for the participants. This dependency structure is often used to analyse interactions in social behaviour, especially the optimisation of economic competition strategies in a free market. The Red Queen model appears to be a useful tool for interpreting political competition phenomena and analysing interactions between political entities. However, there are relatively few references to its analytical applications in political science literature. The article discusses three fundamental issues related to the possibilities of political exploration of the Red Queen hypothesis. Firstly, it presents arguments justifying the use of an evolutionary interpretation for political research. Secondly, it identifies key implications arising from the perception of political competition through the prism of the discussed Leigh Van Halen model. The concepts of competition and cooperation were taken into account, with cooperation being considered a form of coopetition in the political sphere of social life. The final section identifies the key dimensions of analysis for competition among politicians, political parties, and states on the international stage.